Politik Hukum Penetapan Haluan Negara Berdasarkan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 - Widodo, Hananto; Masnun, Muh. Ali (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to analyze legal politics and determine the broad guidelines of state policy based on the 1945 Constitution of the Republic of Indonesia. This study was included in the type of legal study with a statutory approach, a conceptual approach, and a historical approach. The People's Consultative Assembly did not establish the main points of state policy. However, they were jointly formed by the President, the People's Representative Council, and the Regional Representatives Council because the People's Consultative Assembly was no longer located as the highest state institution. The construction of the broad state policy guidelines, designed by the candidate for President or Vice President and his coalition before the general election, was then ratified into law if it had been elected as President. The regulatory period for the state law was designed for five years to make the legal norms more concrete.